Development and application of microsampling approaches. - Protti, Michele (My University, 2023)
The talk presented a comprehensive overview of the Volumetric Absorptive Microsampling (VAMS) approach, including the procedures followed and the results obtained by researchers who have worked on this analytical field in recent years. Various aspects were covered, such as sample collection, handling, and analysis. It may discuss the advantages and limitations of VAMS compared to other microsampling techniques, providing insights into the potential benefits and practical considerations for its implementation. The talk may also showcase specific studies or experiments conducted by different authors, highlighting their methodologies, experimental setups, and the outcomes they achieved. By presenting this information, the talk serves as a valuable resource for scientists seeking to explore and contribute to the field of microsampling.
Keywords: Química analítica - Técnica; Chemistry; Blood; Microsampling; Forensic analysis